Feeling The Elephant's Weight : The Impact of Cote d'Ivoire's Crisis on WAEMU Trade - Egoume Bossogo, Philippe (IMF Working Papers; Working Paper ;, 2011)
This paper analyzes the impact of political instability in Cote d'Ivoire on WAEMU trade over 1990-2007, applying panel econometric techniques to a gravity model of trade within WAEMU and between WAEMU and the rest of the world. The paper finds that intra-regional trade represents a small share of total WAEMU trade and that Cote d'Ivoire accounts for around half of that total, highlighting the importance of this country for the region. The political instability in Cote d'Ivoire has led to an increase in transaction costs, making it relatively more costly for member countries to trade with each other than with the rest of world. Instability has also resulted in a diversion of trade away from Cote d'Ivoire in favor of other countries equipped with ports and in a reduction of WAEMU overall potential trade. For Cote d'Ivoire alone, lost trade is estimated at around 40 percent of its potential trade with the WAEMU in the absence of instability. With a normalization in Cote d'Ivoire, enhanced security and further integration would be essential to achieve higher levels of trade and growth in the WAEMU region.